A Legal Review of the Criminal Acts of Children Performed by Children - M. Hary Angga Pratama (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The crime of murder committed by a child is seen as a crime that takes the life of another person. Children who are shoots, the potential and successor to the ideals of the nation's struggle, of course, cannot be simply punished by the act of murder, he did even though the deed this has taken the lives of other people, considering the function and role of children itself. This paper described a factors that cause criminal acts the murder of children committed by children, legal sanctions for perpetrators of criminal acts child homicide by children, and the role of the police in tackling the crime of child homicide committed by children. This type of research is empirical juridical research, using data from field studies obtained through interviews with M. Ali Ahmadi, as an investigator of the Binjai Police, and also supported by literature study data, so that the data is collected and then analyzed qualitatively. Factors causing the crime of child homicide committed by children consist of factors during the growth of the attitude and mentality of children who are not yet stable, factors family environment, school environment, social environment, and media factors mass or social media. The legal sanction is imprisonment with the threat deducted by the adult penalty. The role of the police in tackling the crime of child homicide, namely preventively is actions taken to prevent or maintain the possibility of occurrence crime. While repressive is an attempt to emphasize the number of crimes by punishing criminals and trying to do the deed by correcting the child offender. The role of the police in tackling the occurrence of child homicides carried out by children, namely, the police should be able to play a more active role in collaborate with other agencies to provide awareness counseling law to the community to better supervise the association of children so as not to fall into the incitement of those around him who are not good, especially related to indication of a murder committed by a child.